1993
DOI: 10.1180/claymin.1993.028.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Pillaring of synthetic hectorite by mixed [Al13-xFex] Pillars

Abstract: The pillaring of a Laponite by alumina pillars, iron pillars and mixed AI-Fe pillars was obtained by a simple in situ method starting from A1CI3 and/or FeCI 3 solutions with different molar ratio Fe/(Fe + AI), and from NaOH solution added simultaneously to the clay suspension. The All 3 pillars were evidenced by XRD and NMR spectra. The density and the charge of these pillars were calculated from the chemical analysis. The Fe pillars (in samples with Fe content >26%) are larger than A113 pillars and slowly red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Intercalation with Al and Fe solutions has been reported in detail by several authors [17][18][19][20][21][22]. Pálinkó et al analyzed the nature of the Al-Fe mixed species generated in pillared clays, by FTIR and Mössbauer spectroscopy, as well as the pillaring agent, and concluded that there is no tetrahedral or octahedral isomorphous substitution of Fe in the Keggin structure of Al 13 .…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Intercalation with Al and Fe solutions has been reported in detail by several authors [17][18][19][20][21][22]. Pálinkó et al analyzed the nature of the Al-Fe mixed species generated in pillared clays, by FTIR and Mössbauer spectroscopy, as well as the pillaring agent, and concluded that there is no tetrahedral or octahedral isomorphous substitution of Fe in the Keggin structure of Al 13 .…”
Section: Introductionmentioning
confidence: 94%
“…The calcined natural bentonite evidences three reduction peaks at around 478, 567 and 691°C. The signal at 478°C corresponds to the reduction of a-Fe 2 O 3 to the Fe 3 O 4 surface iron oxide; the signal at 567°C is associated with the reduction of Fe 3 O 4 to FeO, and the signal at 691°C is related to the reduction of FeO to Fe metal [36,37].…”
Section: Synthesis and Characterization Of Pillared Claysmentioning
confidence: 99%
“…One way to achieve this goal is to introduce mixed-oxide pillars. These materials have been used in isomerization and dehydrogenation reactions: A1-Ga (Viera Coelho and Poncelet, 1991), A1-Zr (Occelli, 1986), A1-Fe (Oades, 1984;Lee et al, 1989;Bergaya et al, 1993), and A1-Cr (Lee et al, 1989). Another possible method to obtain pillared clays with mixed-oxide pillars is to use transition-metal ions by impregnation (Gil and Montes, 1997), with the pillared clay acting as a substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Pillared clays have been prepared also by cation exchange, either before or after initial pillaring of the clay (Suzuki et al, 1988;Carrado et al, 1986). In other cases, pillared clays were prepared by first combining the transition-metal ion with the pillaring agent and the resulting species subsequently used to pillar the clay (Occelli, 1986;Viera Coelho and Poncelet, 1991;Lee et al, 1989;Bergaya et al, 1993;Fetter et al, 1995;Cafiizares et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…(Vaughan and Lussier, 1980;Occelli, 1983;Bergaya et al, 1991) has stimulated research not only for the synthesis of new PILCs, but also for their extensive microscopic characterization. A wide spectrum of analytical techniques, e.g., magic-angle spinning NMR (Plee et al, 1985;Tillak et aL, 1986), EPR (Harsh and Doner, 1984;Braddell et aL, 1987), neutron scattering (Pinnavaia et al, 1984), NMR and HzTPR (Bergaya et al, 1993) and M6ssbauer spectroscopy (Gangas et aL, 1985;Lee Woo et al, 1989;Petridis et al, 1989), has been used for unravelling the structure and the properties of these novel materials. However, in spite of the substantial advance made up to now in the synthesis and characterization of PILCs, the elucidation of additional aspects of the pillared structure (e.g., the diameter of the pillars) is of cardinal importance for understanding the role of their morphology in physicochemical processes occurring in the interlayer space, as well as developing applications,…”
Section: Introductionmentioning
confidence: 99%